Identification of Factors Causing The Increase In Dengue Fever Cases In Pasangkayu Regency - Fivin Ramadani; Aulia Suparman (Journal of Health Science and Pharmacy, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted primarily by Aedes aegypti and Aedes albopictus mosquitoes. In Indonesia, including West Sulawesi Province, the incidence of DHF has shown an increasing trend in recent years. The reported morbidity rate reached 39.25 per 100,000 population, with a case fatality rate (CFR) of 1.13, indicating that DHF remains a significant public health concern. Objectives: This study aims to identify the factors contributing to the increase in DHF cases in Pasangkayu Regency, West Sulawesi Province, in 2022. Method: This study employed a qualitative research approach using secondary data. Data were analyzed through systematic data organization, data display, and interpretative analysis to draw conclusions regarding the contributing factors. Results: The findings indicate that the increase in DHF cases in Pasangkayu Regency was associated with poor environmental sanitation, the effects of climate variability particularly unpredictable rainfall patterns and low levels of community awareness regarding environmental cleanliness and vector control practices. Conclusion: The increase in DHF cases in Pasangkayu Regency highlights the need for comprehensive and integrated dengue control strategies. Strengthening environmental management, improving community participation in vector control activities, and enhancing public awareness through health promotion are essential to reducing DHF transmission. In addition, incorporating climate-based surveillance and early warning systems into dengue prevention programs is crucial for anticipating outbreaks and supporting sustainable disease control efforts.